2022
DOI: 10.3389/fmicb.2022.889788
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Meta-Omics to Provide Modern Microbial Indicators for Monitoring Soil Quality and Securing Food Production

Abstract: Soils are fundamental resources for agricultural production and play an essential role in food security. They represent the keystone of the food value chain because they harbor a large fraction of biodiversity—the backbone of the regulation of ecosystem services and “soil health” maintenance. In the face of the numerous causes of soil degradation such as unsustainable soil management practices, pollution, waste disposal, or the increasing number of extreme weather events, it has become clear that (i) preservin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 158 publications
0
10
0
Order By: Relevance
“…The organic carbon content and the C:N ratio were indeed the main drivers of the soil fungal and bacterial densities taken separately (highlighting the amount and quality of C substrates available for microbial development), but the relative contributions of bacteria and fungi differed, as evidenced by variance partitioning ( Table S1 ). As a consequence, the F:B ratio reflected the complex interactions of these two different functional groups—another key aspect of the understanding of soil microbial communities ( 9 ). Taken together, these results evidence that the F:B ratio provides good complementarity information regarding bacterial and fungal communities, both implied in soil functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic carbon content and the C:N ratio were indeed the main drivers of the soil fungal and bacterial densities taken separately (highlighting the amount and quality of C substrates available for microbial development), but the relative contributions of bacteria and fungi differed, as evidenced by variance partitioning ( Table S1 ). As a consequence, the F:B ratio reflected the complex interactions of these two different functional groups—another key aspect of the understanding of soil microbial communities ( 9 ). Taken together, these results evidence that the F:B ratio provides good complementarity information regarding bacterial and fungal communities, both implied in soil functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences, they have altogether showed good repeatability. However, there is a clear need to standardize methods like the DNA extraction procedure for qPCR ( 8 ) or specific biochemical steps for PLFA analyses ( 7 ) to obtain comparable results across studies or laboratories and evaluate the biological status of soils ( 9 ). A first recent meta-analysis going into this direction focused on 1,323 measurements of the soil F:B ratio using PLFA analyses among 11 major biomes to produce the first global maps of F:B biomass ratios ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges are also applicable to metatranscriptomics, metabolomics, and metaproteomics [ 75 ]. However, these disciplines are largely underexplored for soil microbial communities due to operational challenges [ 76 ]. The challenges motivating these guidelines need to be solved to ensure that the field of soil metagenomics continues to expand.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that functional assignment in this study may not cover all possible functions contributed by the community. Previous studies have demonstrated that fungal functions, predicted by PICRUSt2 and FungalTrait, may be limited by the number of genes available in the database and poor taxonomic classification [ 30 , 31 , 66 ].…”
Section: Discussionmentioning
confidence: 99%